Effects of ethephon and methyl jasmonate on physicochemical properties of Acacia seyal var. seyal (L.) gum produced in Sudan. (May 2019) - Ahmed, Abdelhakam Esmaeil Mohamed; Abdalla, Ashraf Mohamed Ahmed; Kovács, Béla; Yamamoto, Fukuju; Foligni, Roberta; Mozzon, Massimo
Abstract: The study aimed to investigate the effect of two plant growth regulators, namely ethephon (Eth) and methyl jasmonate (Ja-Me) at different concentrations and combinations (1% Eth; 1% Ja-Me; 5% Ja-Me; 1% Eth+1% Ja-Me; and 1% Eth+5% Ja-Me) on physicochemical properties of Acacia seyal var. seyal gums. The study covered two areas within the Sudanese "gum belt" (Shambat and Kenana), thus exemplifying the potentials and problems of gum Arabic production under clay soil in the dryland of Sudan. The results indicated that pedoclimatic conditions (locations) significantly affected gum characteristics; treatments, too, affected physicochemical properties of gum, but in an unpredictable way and with different intensities in the two study areas. Gums obtained by the application of growth regulators, complied with international laws and standards (European Council; Joint FAO/WHO Expert Committee on Food Additives; U.S. Food and Drug Administration; United States Pharmacopeia). Graphical abstract: Image 1 Highlights: Pedoclimatic conditions significantly affect Acacia seyal gum characteristics. Growth regulator treatments affect physicochemical properties of Acacia seyal gums. Treatments mainly affect gum solubilities, metals (Zn, Cu, Fe) and ash contents. Ethephon/jasmonates induced gums comply with international laws and standards.